DISGORGEMENT DALAM MENJAMIN PERLINDUNGAN INVESTOR PASAR MODAL INDONESIA - Vania Regina Artemisia Wijaya; Ariawan Gunadi; Indah Siti Aprilia (PROSIDING SERINA, 2021)
The legal protection of Indonesian capital market investors is still very weak because they are unable to recover losses suffered due to violations of capital market laws and regulations by irresponsible persons. Although the government, both through laws and through the OJK with its regulations, has tried to accommodate investors' financial losses, in fact there is still a regulatory vacuum that is unable to cover losses due to violations that occur. In addition, the procedures that must be followed by investors as victims tend to make it difficult for investors in various aspects and do not even guarantee the certainty that investors can obtain compensation for their lost funds. Things like this encourage the government to innovate in optimizing investor legal protection until OJK adopts the United States' disgorgement concept to be applied in Indonesia by institutionalizing it into PKTS and DKKI supported by POJK Number 65/POJK.04/2020. The research method used is normative legal research with a statutory approach and a conceptual approach. From the research conducted, it is found that PKTS and DKKI are appropriate and relevant steps taken by OJK to achieve corrective justice for both investors and violators. However, the implementation of disgorgement in Indonesia is still not able to provide optimal protection so that it needs to be reviewed, especially with regard to the principles and mechanisms of its implementation.